II Jornada Acadêmica do PPGSBio: Regionalização, biodiversidade e sustentabilidade na Amazônia Setentrional - de Souza Rocha, Gabrielle; Nakashima, Fabiana; Mendonça de Moraes, Cléria (Revista Saúde & Diversidade, 2025)
ABOUT THE EVENT As part of the II Academic Journey of the Graduate Program in Health and Biodiversity (PPGBio), we aim to socialize scientific production in the Northern Amazon, as well as to encourage local, national, and international participation and integration. In this hybrid edition, the theme was Regionalization, Biodiversity, and Sustainability in the Northern Amazon, where members of the academic community who are involved in graduate programs and scientific projects at UFRR had the opportunity to engage in a dialogue. Organizing Committee